Espectroscopia mecânica em tântalo - Barbosa, Geovani Ferreira (Universidade Federal de São Carlos, 2007)
The mechanical spectroscopy technique applied to diffusion studies in body-centered cubic (BCC) metals, such as tantalum. Transition metals, as the tantalum, that has a crystalline structure (BCC), can dissolve large amounts of heavy interstitial solutes, oxygen being an example. In the case of low concentrations, a direct linear relation exists between the maximum height of peaks of internal friction (Q¡1 max) and the concentration of present interstitial solid solution. However, when it is have high concentration of these interstitial elements, an anti-symmetrical broadening of the peak of anelastic relaxation is observed due to the multiple relaxation processes followed by a variation of the temperature which characterizes the metallic matrix-element interstitial interaction. In the present work was observed that the peaks of internal friction which had the Ta-O interaction were not steady and could be occurring the formation of precipitated during the temperature heating cycle. To prove this hypothesis, a large amount of measures were done in different frequencies with a sample of tantalum produced by Escola de Engenharia Química-USP/Lorena. The experimental specters of mechanical relaxation were obtained using the inverted torsional pendulum-type Ke, having an oscillation frequency in the range of 2Hz- 8Hz, temperature heating 300K-700K, with a rate of heating of 1K/min, in better vacuum of 2x10¡6 Torr. These experimental specters Debye elementary peaks through the computational method of successive subtractions making it possible to identify and calculate the mechanical relaxation processes and its parameters (type of interactions, strength of the internal friction peak, temperature of peak, energy of activation and time relaxation). Finally, the following complementary analysis were also used to: X-ray diffraction measures, analysis of the oxygen concentration, metallographic analysis using optical and scanning electronic microscope, and energy dispersive spectroscopy (EDS).
Keywords: Física; Espectroscopia mecânica; Tântalo; Difusão; Gases em metais; CIENCIAS EXATAS E DA TERRA::FISICA